PERENCANAAN PENGGANTIAN JEMBATAN TINJOMOYO KOTA SEMARANG - Indra Hadi Mulyaning Wahyu; Kurmein Al Musadad; Moga Narayudha; Rudi Yuniarto Adi (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
The purpose of planning the replacement of the bridge is the first Tinjomoyo to the facilitate public access Tinjomoyo an increasingly crowded, and then to replace the steel bridge that was damaged because there is no control of the government for the cost of care is expensive and prone to corrosions and there fore the government has an alternative to replace the bridge permanently by using concrete bridge or concrete because of soil condition in the area tinjomoyo including hard ground and there fore the selection of the palm of shallow foundation and wells as a load – bearing, but it is not concrete in terms of treatment need special care such as steel concrete bridge corrosions. Event not experience in bridge construction is needed time of 32 weeks.